Industrial Perspective on Hydrogen Purification, Compression, Storage, and Distribution. Issue 4 (3rd August 2020) - Peschel, A.
Abstract: Green hydrogen production by electrolysis using renewable power allows for decoupling the time and location of hydrogen production and use. Even if pipeline transport of hydrogen is most economic for large scale, transport by trailers will be present in near and mid‐term future since the construction of a hydrogen pipeline network will take a long time. Furthermore, the volume of trailer transport will increase with increasing hydrogen demand raising the question what the best hydrogen carrier is. Within this contribution, different hydrogen carriers are compared regarding their energy efficiency and their practicability. In addition, an overview of hydrogen compression technology is given including piston, membrane, screw, electrochemical, thermal, and turbo compressors. As hydrogen carriers, gaseous compressed hydrogen (CGH), liquid hydrogen, (LH2), liquid organic hydrogen carriers (LOHC), metal organic frameworks (MOF), hydrides and ammonia are evaluated. CGH is most energy efficient for short transport distances, but for longer distances a higher hydrogen density is required. Here, LH2 and LOHCs compete both showing a high hydrogen density. However, if larger hydrogen liquefiers are built in future, LH2 is more practical due to its better energy efficiency (at least for fueling station supply) and proven technology readiness.